Association of foot-and-mouth disease (FMD) virus vaccine elicited immune response with productive and reproductive performance in crossbred cattle - GOWANE, G R; SHARMA, A K; SANKAR, M; VANDRE, R; THIRUMURUGAN, P; SUBRAMANIAM, S; PATTNAIK, B (The Indian Journal of Animal Sciences, 2013)
FMD is one of the most contagious diseases of cloven-hoofed farm animals and remains a major threat to animal husbandry. In India, vaccination with the inactivated trivalent (O, A and Asia1) vaccine for the control of FMD is one proven way for protecting the livestock. In this study we tried to find the relationship between production and reproduction parameters of the crossbred cattle with FMD virus vaccine elicited immune response. In the present herd, average 305 days milk yield and daily protein yield was 2244.83 Â± 80.44 kg and 2.98 Â± 0.017 g, respectively. Study revealed that the vaccine response and 305 day milk yield as well as protein yield are independent of each other and they do not affect occurrence of each other. However, the association between vaccine response and part milk yield in crossbred cattle were significant in the present study. Those cattle that were in their first trimester of lactation had lower antibody titer to the FMD virus vaccine as compared to the later part of lactation or non-lactating cattle. Results of this study define the variation in vaccine response for part lactating yield; however repeated studies in different herds and locations are mandatory to avoid probability of association by chance